BODY TRANSFORMATION FOR 5 WEEKS USING A FITNESS-BOXING METHOD - Kalpachki, Blagoy (Revista Observatorio del Deporte, 2020)
In today’s lifestyle, in the context of globalization, industrialization and urbanization, the physical activity of the population (globally) has decreased significantly. This reality creates serious preconditions for the deterioration of a person’s health status.As a result of reduced physical activity, unhealthy eating, stress, etc., one of the most common metabolic disorders, which poses serious health risks -obesityhas increased significantly.The current research focuses on the impact of a self-developed fitness boxing technique (5 weeks) for body transformationin 18-32 year old women. The results of an empirical study conducted in the period from 2012 to 2019 are presented, which objectify the effectiveness of the applied fitness-boxing methodology, as a means of burning unnecessary body fat and shaping a beautiful and aesthetic body.